SYNTHESIS AND CONFORMATION OF p-(AMINO)BUTOXYCALIX[4]ARENE - Firdaus Firdaus; Jumina Jumina; Hardjono Sastrohamidjojo (Universitas Gadjah Mada, 2007)
Derivatization of 5,11,17,23-tetra-t-butyl-25,26,27,28-tetrahydroxycalix[4]-arene to 5,11,17,23-tetra-amino-25,26,27,28-tetrabutoxycalix[4]arene compound via etherification, ipso nitration, and reduction reactions, respectively has been conducted. The etherification reaction was carried out by refluxed the mixture of 5,11,17,23-tetra-t-butyl-25,26,27,28-tetrahydroxy-calix[4]arene, 1-bromobutane, NaI, and NaH in solvent mixture of THF-DMF (10:1 v/v) and nitrogen atmosphere for 4 hours to resulted 5,11,17,23-tetra-t-butyl-25,26,27,28-tetrabutoxycalix[4]-arene 84% in yield; ipso nitration reaction was carried out by stirred the mixture of 5,11,17,23-tetra-t-butyl-25,26,27,28-tetrabutoxycalix[4]arene and HNO3 100% in solvent mixture of dichloromethane-acetic acid glacial (1:1 v/v) for 2 hours and than refluxed for 1 hour to resulted 5,11,17,23-tetra-nitro-25,26,27,28-tetra-butoxycalix[4]arene 50% in yield; and reduction reaction was carried out by refluxed the mixture of 5,11,17,23-tetra-nitro-25,26,27,28-tetrabutoxycalix[4]arene and SnCl2/HCl reductor in ethanol solvent for 6 hours to resulted 5,11,17,23-tetra-amino-25,26,27,28-tetrabutoxycalix[4]arene 67% in yield. In the etherification reaction, the conformation of calix[4]arene compound was converted from cone to partial cone; but in the followed reactions, i.e. nitration and reduction reactions, the conformation of calix[4]arene compounds were remain in partial cone.